2020
DOI: 10.1039/d0ra04189k
|View full text |Cite
|
Sign up to set email alerts
|

A faster and more effective chrome tanning process assisted by microwave

Abstract: In leather manufacturing, microwave usually has the ability to strengthen the combination between collagen and chemicals and make the corresponding procedures faster and more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Other similar studies conducted by Yorgancioglu et al and Ferdous et al also reported the shrinkage temperature of chrome-tanned leather which was 103.5 °C [40] and 105 to 110 °C [41]. Interestingly, the shrinkage temperatures of all manufactured goat leather from the present study were considerably higher than the data reported previously in the literature [40][41][42] following the conventional method which demonstrated that the leather processed with recovered basic chromium salts was hydrothermally more stable.…”
Section: Hydrothermal Stability (Shrinkage Temperature)supporting
confidence: 59%
“…Other similar studies conducted by Yorgancioglu et al and Ferdous et al also reported the shrinkage temperature of chrome-tanned leather which was 103.5 °C [40] and 105 to 110 °C [41]. Interestingly, the shrinkage temperatures of all manufactured goat leather from the present study were considerably higher than the data reported previously in the literature [40][41][42] following the conventional method which demonstrated that the leather processed with recovered basic chromium salts was hydrothermally more stable.…”
Section: Hydrothermal Stability (Shrinkage Temperature)supporting
confidence: 59%
“…In addition, manufacturers add intentionally metals or metallic compounds to textile products to achieve or improve specific functionalities. As example, approximately 80% of leathers are chrome-tanned [ 1 , 2 ], while vanadium, chromium, barium, lead, copper, cobalt, and nickel are used in textile dyeing [ 3 , 4 ], and iron and manganese are used in bleaching processes [ 5 , 6 ]. In addition, antimony compounds have been demonstrated to enhance the flame retardant properties of halogen compounds and commonly flame-retardant compounds used in textiles preparation [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…FT-IR results showed that the collagen type I structure including helical structure was maintained when the modified extraction was used to promote the process. 57–60…”
Section: Resultsmentioning
confidence: 99%